A Comprehensive Systematic Review of The Relationship between Epstein-Barr Virus (EBV) Exposure and the Development of Non-Keratinizing Nasopharyngeal Carcinoma - Muhammad Rifki Kholis Putra; Muhammad Abduh Firdaus (The International Journal of Medical Science and Health Research, 2026)
Introduction: Nasopharyngeal carcinoma (NPC) is a malignancy with a distinct geographical distribution, showing high prevalence in endemic regions like Southern China and Southeast Asia. The Epstein-Barr virus (EBV) is a well-established oncogenic driver, particularly for non-keratinizing NPC subtypes (WHO Types II/III). Understanding the precise relationship between EBV exposure, its biomarkers, and NPC development is critical for improving early detection, prognosis, and treatment strategies (Banko et al., 2021; Chan et al., 2004). Methods: This report synthesizes evidence from a systematic review of 80 sources, including meta-analyses, cohort studies, randomized controlled trials, and case-control studies. Data extraction focused on study design, population characteristics, EBV exposure definition (serological markers, plasma EBV DNA, genetic variants), NPC histological classification, measures of association, confounders, and study quality. Quantitative synthesis was performed on diagnostic accuracy, prognostic value, and screening effectiveness. Results: The evidence demonstrates a near-universal association between EBV and non-keratinizing NPC in endemic regions, with EBV positivity rates reaching 100%. Serological markers like VCA-IgA show high diagnostic accuracy (pooled sensitivity 0.91, specificity 0.92), with multi-marker panels (e.g., VCA-IgA + EA-IgA + Rta-IgG) providing superior performance. Plasma EBV DNA detection offers excellent diagnostic (sensitivity 89.1%, specificity 85.0%) and superior prognostic utility. High-risk EBV genetic variants (e.g., BALF2 I613V, OR=7.9) are strongly linked to NPC risk. Pre-treatment and, more powerfully, post-treatment plasma EBV DNA levels are significant independent prognostic factors for overall, progression-free, and distant metastasis-free survival (e.g., HR up to 129.07 for post-treatment DNA). EBV-based screening programs in endemic areas have demonstrated a significant 30% reduction in NPC mortality (Chen et al., 2024). Discussion: The robust association underscores EBV's central role in non-keratinizing NPC carcinogenesis. The diagnostic and prognostic hierarchy favors plasma EBV DNA and multi-parameter serology. Geographic, methodological, and histological heterogeneity explain variations in reported associations. EBV biomarkers are pivotal for risk stratification, screening, treatment monitoring, and prognostication. Conclusion: EBV is a fundamental etiological agent for non-keratinizing NPC. Integrating EBV serology and plasma EBV DNA into public health screening programs in endemic regions and into clinical management protocols for diagnosis, prognostic stratification, and treatment monitoring is strongly supported by evidence. Future research should focus on standardizing assays, elucidating molecular mechanisms, and validating findings in non-endemic populations.